Human Embryonic Stem Cell-Derived Cardiomyocytes Regenerate Non-Human Primate Hearts - Chong, James J.H. (2014)
Pluripotent stem cells provide a potential solution to current epidemic rates of heart failure (1) by providing human cardiomyocytes to support heart regeneration (2). Studies of human embryonic stem cell-derived cardiomyocytes (hESC-CMs) in small animal models have shown favorable effects of this treatment (3–7). It remains unknown, however, whether clinical scale hESC-CMs transplantation is feasible, safe or can provide large-scale myocardial regeneration. Here we show that hESC-CMs can be produced at a clinical scale (>1 billion cells/batch) and cryopreserved with good viability. Using a non-human primate (NHP) model of myocardial ischemia-reperfusion, we show that that cryopreservation and intra-myocardial delivery of 1 billion hESC-CMs generates significant remuscularization of the infarcted heart. The hESC-CMs showed progressive but incomplete maturation over a three-month period. Grafts were perfused by host vasculature, and electromechanical junctions between graft and host myocytes were present within 2 weeks of engraftment. Importantly, grafts showed regular calcium transients that were synchronized to the host electrocardiogram, indicating electromechanical coupling. In contrast to small animal models (7), non-fatal ventricular arrhythmias were observed in hESC-CM engrafted primates. Thus, hESC-CMs can remuscularize substantial amounts of the infarcted monkey heart. Comparable remuscularization of a human heart should be possible, but potential arrhythmic complications need to be overcome.